Cell-based therapeutic products: potency assay development and application. (July 2014) - Basu, Joydeep; Ludlow, John W
Potency is a critical quality attribute of biological products, defined by the US FDA as the specific ability or capacity of the product, as indicated by appropriate laboratory tests or by adequately controlled clinical data obtained through the administration of the product in the manner intended, to effect a given result. Ideally, a potency assay will leverage the product's mechanism of action. Alternatively, the assay may focus on a therapeutically relevant biological activity. The absence of rigorous mechanistic data for the majority of cell-based therapeutics currently in the process research pipeline has impeded efforts to design and validate indices of product potency. Development of a systematic battery of parallel functional assays that, taken together, can address all potential mechanisms of action believed to be relevant for the product platform is recommended. Such an approach is especially important during preclinical development. Here, we summarize the principal and unique challenges facing the development of functionally relevant and rigorous potency assays for cell-based therapeutics. We present perspectives regarding potency assay development for these products as illustrated by our experiences in process R&D of cryopreserved hepatocytes (Incara Pharmaceuticals) and selected renal cells (Tengion).